Functional analysis of the whole CYPome and Fdxome of Streptomyces venezuelae ATCC 15439 - Shuai Li; Zhong Li; Guoqiang Zhang; Vlada B. Urlacher; Li Ma; Shengying Li (Engineering Microbiology)
Cytochrome P450 enzymes (CYPs or P450s) and ferredoxins (Fdxs) are ubiquitously distributed in all domains of life. Bacterial P450s are capable of catalyzing various oxidative reactions with two electrons usually donated by Fdxs. Particularly in Streptomyces, there are abundant P450s that have exhibited outstanding biosynthetic capacity of bioactive metabolites and great potential for xenobiotic metabolisms. However, no systematic study has been conducted on physiological functions of the whole cytochrome P450 complement (CYPome) and ferredoxin complement (Fdxome) of any Streptomyces strain to date, leaving a significant knowledge gap in microbial functional genomics. Herein, we functionally analyze the whole CYPome and Fdxome of Streptomyces venezuelae ATCC 15439 by investigating groups of single and sequential P450 deletion mutants, single P450 overexpression mutants, and Fdx gene deletion or repression mutants. Construction of an unprecedented P450-null mutant strain indicates that none of P450 genes are essential for S. venezuelae in maintaining its survival and normal morphology. The non-housekeeping Fdx1 and housekeeping Fdx3 not only jointly support the cellular activity of the prototypic P450 enzyme PikC, but also play significant regulatory functions. These findings significantly advance the understandings of the native functionality of P450s and Fdxs as well as their cellular interactions.